Soft multihadron dynamics - Kittel, W. (World Scientific, 2005)
This book gives a comprehensive account of the development and present status of the field of soft (i.e. non-perturbative) phenomena encountered in the production of (multi- ) hadronic final states by the collision of various types of particles at high energies. Phenomenological models used to describe the data are in general inspired by Quantum Chromo Dynamics (QCD) and the book repeatedly crosses the border if at all existent between soft (non-perturbative) and hard (perturbative) QCD.